Growth of a Highly Porous Coordination Polymer on a Macroporous Polymer Monolith Support for Enhanced Immobilized Metal Ion Affinity Chromatographic Enrichment of Phosphopeptides. (14th July 2014) - Saeed, Adeela; Maya, Fernando; Xiao, Dianne J.; Najam‐ul‐Haq, Muhammad; Svec, Frantisek; Britt, David K.
<x xml:space="preserve">Abstract</x> A simple room temperature solution‐based method for the preparation of highly porous iron(III) benzenetricarboxylate coordination polymer films on the internal surface of a macroporous polystyrene‐divinylbenzene‐methacrylic acid polymer is reported. The resulting metal‐organic polymer hybrid (MOPH) maintains a high specific micropore surface area of 389 m2 g‐1 and thermal stability above 250 °C in air. The MOPH preparation is readily adapted to a capillary column, yielding a flow‐through separation device with excellent flow permeability and modest back‐pressure. The excellent separation capability of the MOPH column is demonstrated by enriching phosphopeptides from mixtures of digested proteins. This approach to MOPH synthesis is easily implemented and likely adaptable to a wide range of coordination polymers and metal‐organic frameworks.